Management of toxicants and anti-nutritional factors in poultry feed - Singh, Ram; Biswas, Avishek; Sharma, Divya; Mandal, A B (Indian Farming, 2019)
Presence of mycotoxins and anti-nutritional factors (ANFs) in poultry feed is one of the major constraints in utilization and maintaining feed quality as the mycotoxins are widely present in feedstuffs and ANF are inherent component of feedstuffs. Mycotoxins are low molecular weight secondary metabolites produced by certain strains of filamentous fungi such as Aspergillus, Penicillium and Fusarium, which invade crops in the field and may grow on food during storage under favourable conditions of temperature and humidity. The occurrence of mycotoxins in agricultural commodities depends on region, season and the conditions under which particular crop is grown, harvested or stored.